2017
DOI: 10.2147/ndt.s119208
|View full text |Cite
|
Sign up to set email alerts
|

Impact of parental presence during induction of anesthesia on anxiety level among pediatric patients and their parents: a randomized clinical trial

Abstract: IntroductionAnesthesia induction is a stressful event for children and their parents, and may have potentially harmful consequences on the patient’s physiological and mental situation. Stressful anesthesia induction has psychological adverse effects that recur with repeated anesthesia, can lead to increased pediatric discomfort during the recovery period, and may even induce reactionary postoperative behavior. A randomized controlled trial was performed to assess the impact of parental presence during inductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
30
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 15 publications
(23 reference statements)
7
30
0
6
Order By: Relevance
“…Moreover, the anxiety of the children increased as they advance through the preoperative stages towards the operating theatre, with separation from the parents being the moment at which most patients experienced PAO, even though the moment of anaesthetic induction is that at which the anxiety score is highest. Earlier studies have also indicted that the moment of anaesthetic induction as that at which anxiety is maximal 4,14,22 . The discrepancy between the time points with the maximum PAO scores and the highest proportion anxiety patients in our study can be explained by the fact that the parents are separated from their children when they enter the operating theatre, while in many of the studies reviewed the parents remain with their children until the moment of anaesthetic induction 4,5,[iv] .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the anxiety of the children increased as they advance through the preoperative stages towards the operating theatre, with separation from the parents being the moment at which most patients experienced PAO, even though the moment of anaesthetic induction is that at which the anxiety score is highest. Earlier studies have also indicted that the moment of anaesthetic induction as that at which anxiety is maximal 4,14,22 . The discrepancy between the time points with the maximum PAO scores and the highest proportion anxiety patients in our study can be explained by the fact that the parents are separated from their children when they enter the operating theatre, while in many of the studies reviewed the parents remain with their children until the moment of anaesthetic induction 4,5,[iv] .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported the effect of parental presence on the day of surgery and during the induction period, which could reduce the child's preoperative anxiety level [33][34][35] . Regarding the hospital's policy, parents were allowed to stay with their children since arrival at the preoperative holding area until starting induction at the operating room.…”
Section: Discussionmentioning
confidence: 99%
“…It is noted that 40 to 60 per cent of children having surgical procedures suffer high levels of anxiety 1 . Anaesthetic induction can be extremely stressful for children and it may have damaging effects on the child's physiological and mental health 2 . There have been advances in the management of anxiety in paediatric anaesthesia.…”
Section: Introductionmentioning
confidence: 99%